2015
DOI: 10.5301/jva.5000389
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of PICC Complications in Orthopedic Inpatients with Bone Infection for Long-Term Intravenous Antibiotics Therapy

Abstract: Even in orthopedic patients with chronic orthopedic bone infection, PICCs have a low rate of complication. The increasing lumen number of the PICC is a potential risk factor in our series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 17 publications
1
24
1
1
Order By: Relevance
“…Across several studies, pain during catheter insertion was reported in 0% to 18% of patients using PICCs. [11][12][13][14][15] In the study by Konstantinou et al, 11 no significant difference was reported for pain during the procedure between PICCs and CICCs (7.7% vs. 12.2%, P = 0.502). In the study by Pedersen et al, 14 8.7% of patients with PICCs experienced pain during insertion, compared to 23.4% of patients with PIVC lines.…”
Section: Efficacy Outcomesmentioning
confidence: 90%
See 2 more Smart Citations
“…Across several studies, pain during catheter insertion was reported in 0% to 18% of patients using PICCs. [11][12][13][14][15] In the study by Konstantinou et al, 11 no significant difference was reported for pain during the procedure between PICCs and CICCs (7.7% vs. 12.2%, P = 0.502). In the study by Pedersen et al, 14 8.7% of patients with PICCs experienced pain during insertion, compared to 23.4% of patients with PIVC lines.…”
Section: Efficacy Outcomesmentioning
confidence: 90%
“…The rates of removal due to complications were 3.5% to 48% with PICCs [4][5][6]12,14,15,20,[23][24][25][26][27]29,32,33,35,37,38,45,46 compared to 67% to 81.2% with PIVCs 6,14 and 26% to 78% with CICCs. 5,6,33 In the study by Cotogni et al 5 in which catheters were used for home parenteral nutrition in patients with cancer, the ratio of complications leading to removal over total complications was significantly lower for PICCs versus CICCs (55% vs. 85%, P < 0.05).…”
Section: Safety Outcomesmentioning
confidence: 94%
See 1 more Smart Citation
“…However, intravenous therapy carries substantial risks, and it is inconvenient for patients [2]. In particular, long-term intravenous antibiotic therapy may cause complications such as catheter-related bloodstream infections and thrombosis [3]. Currently, the mainstay treatment method is debridement followed by systemic antibiotic therapy, which commonly includes intravenous infusion for 2 weeks followed by oral antibiotics for 4-6 weeks [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…However, intravenous therapy carries with it substantial risks and it is inconvenient for patients [2]. In particular, long-term intravenous antibiotics therapy may bring the complication of catheter-related bloodstream infections and thrombosis [3]. Currently, the mainstream treatment method is debridement followed by systemic antibiotics therapy, which is commonly intravenous infusion for two weeks followed by oral antibiotics for 4-6 weeks [4,5].…”
Section: Introductionmentioning
confidence: 99%